Application of EEG/ERP and Eye Tracking in Underlying Mechanism of Visual Attention of Auto Dealer’s Advertisement – A Neuromarketing Research - Samsuri, Norlyiana; Reza, Faruque; Begum, Tahamina; Yusoff, Nasir; Idris, Badrisyah; Omar, Hazim; Mohd Isa, Salmi (International Journal of Engineering and Technology, 2018)
This study aims to detect the level of attention and gaze behavior on diverse display design of advertisement through the applications of Event Related Potential (ERP) and Eye Tracking. Total of 15 subjects participated in ERP, while two subjects (out of 15) participated in Eye Tracking. The N200 ERP component was recorded using 128-sensor net. The result of the ERP and gaze behavior showed consistent results that subjects were more attentive to the Vertex Reared Grouped (VRG) view compared to Vertex Frontal Grouped (VFG) view, and more attentive to the Right Lateral Grouped (RLG) view compared to Left Lateral Grouped (LLG) view in Session 1 and Session 3 respectively. Visual interpretation of scan path together with fixation duration and saccade duration of gaze behavior data revealed that VRG view and RLG view attracted more attention than its counterpart. For Session 2, the results of the ERP and gaze behavior indicated that subjects were equally attentive to the Right Lateral Singular (RLS) view and Left Lateral Singular (LLS) view. Gaze behavior showed that scan path during RLS view and LLS view indicated similar amount of gaze in both display designs. For cost-effective and limited space advertising, it is advisable that marketers prioritize display design of VRG view than its counterpart and RLG view than its counterpart.Â